Oemar Bakry's Tafsir Madrasi: Moral Education Themes in Surah Al-Baqarah and Contemporary Relevance - Rochmad Rochmad; Dinda Aisyah Wahid; Tasya Putri Nurhayat; Averosian Sophia Madany; Mahmud Rifaannudin; Muhammad Badrun (International Journal of Nusantara Islam, 2026)
This study analyzes the concept of moral education in Tafsir Madrasi by Oemar Bakry, focusing on Surah al-Baqarah verses 1-63 and 142-249. This study aims to uncover the moral values ​​articulated by Bakry in the Qur'an and their relevance to the contemporary Islamic education paradigm. This study uses a qualitative-descriptive method with a thematic interpretation (maudu'i) approach, supported by an analysis of Islamic education theory. The findings indicate that Oemar Bakry views moral education as a holistic personality formation process that instills the values ​​of faith (iman), trust (amanah), patience (ṣabr), justice ('adl), and piety (taqwa). These values ​​serve as a conceptual foundation for curriculum design, humanistic teaching methods, and the development of moral leadership in modern education. Theoretically, this study contributes to the development of an integrative Islamic education paradigm that combines spiritual, rational, and social dimensions, consistent with contemporary value-based education theory. Therefore, the Madrasi Interpretation is not just a classical Indonesian interpretation, but also a conceptual reference for the development of Islamic education that is value-oriented and civilized.